1996
DOI: 10.1128/jb.178.7.1821-1828.1996
|View full text |Cite
|
Sign up to set email alerts
|

Systematic mutagenesis of the active site omega loop of TEM-1 beta-lactamase

Abstract: ␤-Lactamase is a bacterial protein that provides resistance against ␤-lactam antibiotics. TEM-1 ␤-lactamase is the most prevalent plasmid-mediated ␤-lactamase in gram-negative bacteria. Normally, this enzyme has high levels of hydrolytic activity for penicillins, but mutant ␤-lactamases have evolved with activity toward a variety of ␤-lactam antibiotics. It has been shown that active site substitutions are responsible for changes in the substrate specificity. Since mutant ␤-lactamases pose a serious threat to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
66
0
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 36 publications
8
66
0
1
Order By: Relevance
“…D179 and R164 form a salt bridge and are the anchor points of the omega loop that contains the catalytically important E166 (20). Disruption of this salt bridge leads to extension of the substrate profile (2,28). For unknown reasons, many natural TEM ESBLs are altered in position 164 (22), but none are altered in position 179, while in SHV ESBLs the opposite is true.…”
Section: Discussionmentioning
confidence: 99%
“…D179 and R164 form a salt bridge and are the anchor points of the omega loop that contains the catalytically important E166 (20). Disruption of this salt bridge leads to extension of the substrate profile (2,28). For unknown reasons, many natural TEM ESBLs are altered in position 164 (22), but none are altered in position 179, while in SHV ESBLs the opposite is true.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting that laboratory mutants of TEM-1 that contain mutations at positions other than the ones described in nature have been constructed (18,130,180,182). It has been suggested that the naturally occurring TEM-type ESBLs are the result of fluctuating selective pressure from several ␤-lactams within a given institution rather than selection with a single agent (18).…”
Section: Temmentioning
confidence: 99%
“…The agar plates containing 1 mg/ml ampicillin were used to select clones from the library that provide wild-type levels of ampicillin resistance because this is the highest concentration of ampicillin on which an E. coli cell containing the TEM-1 plasmid can grow (33,34). The plates were then incubated at 37°C overnight.…”
Section: Construction Of the Position 170 Random Library And Selectiomentioning
confidence: 99%